Homicide and Associated Steroid Acute Psychosis: A Case Report - G. Airagnes; C. Rouge-Maillart; J.-B. Garre; B. Gohier (Case Reports in Medicine)
We report the case of an old man treated with methylprednisolone for chronic lymphoid leukemia. After two months of treatment, he declared an acute steroid psychosis and beat his wife to death. Steroids were stopped and the psychotic symptoms subsided, but his condition declined very quickly. The clinical course was complicated by a major depressive disorder with suicidal ideas, due to the steroid stoppage, the leukemia progressed, and by a sudden onset of a fatal pulmonary embolism. This clinical case highlights the importance of early detection of steroid psychosis and proposes, should treatment not be stopped, a strategy of dose reduction combined with a mood stabilizer or antipsychotic treatment. In addition have been revised the risks of the adverse psychiatric effects of steroids.